ANALISIS PENGARUH PERSEPSI HARGA, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Rustina Dewi Werdiasih; Nandang Bekti Karnowati; Yoana Yoana (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2022)
The beauty product industry is currently growing. The emergence of various beauty product brands requires the Scarlet company to have a strategy in facing market competition. The purpose of the study was to determine the effect of price perception, brand image and product quality on Scarlett's purchasing decisions. Data was collected by filling out questionnaire answers to 100 consumers who had used Scarlett products. Data were analyzed by PLS SEM and samples were taken using non-probability sampling method. The findings show that the variables of price perception, brand image and product quality have a direct effect on purchasing decisions. Product quality variable has a direct impact on brand image, but price perception does not have a direct impact on brand image. The brand image variable mediates the connection of product quality on purchasing decisions, but brand image does not mediate the relationship between price perceptions and purchasing.